ANALISIS KANDUNGAN PROTEIN DAN LEMAK PADA TERIPANG PASIR (Holothuria scabra) YANG DIPEROLEH DARI PERAIRAN DESA SULI DAN APLIKASINYA KEPADA MASYARAKAT MELALUI PENYULUHAN - Renyaan, Angelica Jenita Felisitas; Tuaputty, Hasan; Rumahlatu, Dominggus (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: One kind of animals with spines are sea cucumbers. Sandy waters, rocky or muddy beaches, and coral reefs are common habitats for these species. Clear, clean waters with a fine sandy bottom, away from pounding waves, are ideal for the growth of sand sea cucumbers. Sea cucumbers are found in great number across Maluku. One such location is the waters surrounding Suli village, where sand sea cucumbers, or Holoturia scabra, are particularly common. Methods: Descriptive approaches are used in this study. The laboratory study findings served as the basis for the data sources. Results: In samples of sand sea cucumbers (Holothuria scabra), the protein yield was greater than the fat content. Conclusion: The protein content is 15.3544 and the fat content is 0.1816. This protein level figure is still below the maximum protein threshold of 72.93%.